Overexpression of Acyl-CoA-Binding Protein 1 (ChACBP1) From Saline-Alkali-Tolerant Chlorella sp. Enhances Stress Tolerance in Arabidopsis - Qiao, Kun; Wang, Min; Takano, Tetsuo; Liu, Shenkui (Frontiers in Plant Science, 2018)
A large proportion of the world's arable land is saline-alkali land, and this is becoming an urgent environmental problem for agriculture. One approach to address this problem is to develop new varieties of stress-resistant plants through genetic engineering. The alga (Chlorella sp.) JB6, which was previously isolated from saline-alkali land, was found to exhibit strong NaHCO3 tolerance. Here, we explored saline-alkali-tolerance (SAT) genes in this alga that might be useful for producing abiotic stress-resistant transgenic plants. We identified a gene encoding acyl-CoA-binding protein 1 (ACBP1) from JB6 by screening a full-length cDNA library in yeast under NaHCO3 stress. Northern blot analyses showed that the ChACBP1 mRNA levels were significantly up-regulated under abiotic stresses such as salinity, oxidation, heavy metals, and low temperature stresses. The recombinant ChACBP1 protein was found to bind phosphatidylcholine in vitro. Green fluorescent protein-labeled ChACBP1 was localized to the cytosol. Overexpression of ChACBP1 in yeast and Arabidopsis increased their resistance to high salinity, oxidation, heavy metals, and low temperature stresses. These results suggested that ChACBP1 may mediate plant abiotic stress adaptation through phospholipid metabolism. Thus, ChACBP1 may be useful to genetically improve the tolerance of plants to saline-alkali soil.